Analysis of Water Quality Pollution in The Tempur River Based On TDS, TSS, Temperature, and Color Parameters - Khasanah, Ulfa Niswatul; Alfika, Rifqia Rahma Alfika (Indonesian Journal of Engineering, Science and Technology, 2025)
This study aims to analyze the level of water pollution in the Tempur River based on physical parameters, including Total Dissolved Solids (TDS), Total Suspended Solids (TSS), temperature, and color. The Tempur River is one of the water sources used by the surrounding community, so it is important to know its water quality condition. Sampling was carried out at several strategic points along the river. Laboratory analysis was performed to measure TDS, TSS, temperature, and water color intensity, then compared with the quality standards set in Government Regulation No. 22 of 2021 regarding Water Quality and Water Pollution Control. The temperature, TDS, and color parameters of the Tempur River are still within the quality standard limits set by Government Regulation No. 22 of 2021 The results show that the water temperature of 28.9°C is within the normal range but close to the upper limit, potentially influenced by high sunlight intensity, low vegetation shading, and shallow river depth. The TDS level of 305 mg/L is well below the maximum threshold of 1000 mg/L, indicating that dissolved substances are within safe limits, though minor anthropogenic activities may contribute to this value. The TSS concentration of 35 mg/L is below the allowable limit set by Government Regulation No. 82 of 2001, suggesting the water is relatively clear and suitable for agricultural and fishery use. Furthermore, the water color value of 15.0 Pt-Co is significantly below the threshold of 50 Pt-Co, indicating clear water with minimal pollution from dissolved organic compounds or industrial waste. Overall, the water quality of the Tempur River remains within acceptable limits, though ongoing monitoring is recommended to maintain its suitability for various uses. Keywords- Color Parameter; TDS; Temperature; Tempur River; TSS; Water Pollution.